2019
DOI: 10.2478/fhort-2019-0022
|View full text |Cite
|
Sign up to set email alerts
|

Cultivation of dandelion (Taraxacum erythropodium) on coastal saline land based on the control of salinity and fertilizer

Abstract: Dandelion (Taraxacum spp.) is a widely distributed weed; in China, however, dandelion has been considered to be a kind of medicinal and edible vegetable in recent years. This transition from weed to vegetable requires corresponding cultivation and management. Thus, the production of dandelion on saline land was conducted based on the evaluation of dandelion salt tolerance. Low soil salt content (< 0.3%) did not significantly affect dandelion growth, and the salt tolerance threshold of dandelion ranged from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 16 publications
4
12
0
Order By: Relevance
“…Available data on the salinity tolerance of the tested species are scarce in the literature. However, in agreement with our results, high salt content in soil (>0.7%) significantly reduced plant growth in Taraxacum erythropodium, whereas at salt content below 0.7% the declining trend weakened [45]. On the other hand, there is evidence that R. picroides is resistant to high salinity levels, as its natural habitats include saline sand dunes in the coastal areas of the Mediterranean [75], while other reports indicate the effectiveness of the species to withstand saline irrigation water of 8 dS m −1 without significantly compromising plant growth [46].…”
Section: Plant Growthsupporting
confidence: 92%
See 3 more Smart Citations
“…Available data on the salinity tolerance of the tested species are scarce in the literature. However, in agreement with our results, high salt content in soil (>0.7%) significantly reduced plant growth in Taraxacum erythropodium, whereas at salt content below 0.7% the declining trend weakened [45]. On the other hand, there is evidence that R. picroides is resistant to high salinity levels, as its natural habitats include saline sand dunes in the coastal areas of the Mediterranean [75], while other reports indicate the effectiveness of the species to withstand saline irrigation water of 8 dS m −1 without significantly compromising plant growth [46].…”
Section: Plant Growthsupporting
confidence: 92%
“…Moreover, the increased leaf K concentration (7.04% DW) determined in R. picroides compared to the leaf K (5.48% DW) of T. officinale (Table 3) could be related to the higher proline biosynthesis in R. picroides, since Chou et al [114] mentioned that proline accumulation depends on the availability of potassium. As mentioned before, in both species, proline content in EC-6 treatment did not differ from the control; however, the increase in T. officinale was more profound than that in R. picroides, a finding which is in agreement with the results of Wu et al [45], who reported that Taraxacum erythropodium plants exhibited a rapid response to the increased salinity by increasing leaf proline content. Similar results were reported by Slabbert and Krüger [115] for Amaranthus sp., Xue et al [113] for Brassica napus and Saleh [116] for Vigna radiata plants.…”
Section: Proline Contentsupporting
confidence: 91%
See 2 more Smart Citations
“…It is a kind of edible medicinal plant, and people often extract lutein from its flowers due to very high carotenoids. However, marigold leaf extract can inhibit the growth of cancer cells and bacteria mainly because of chemical compounds like flavones, chlorogenic acid, and coffee acid which functioned as antibacterial, anti-inflammatory, and antioxidant effects [10,11]. After the extraction of carotenoids from the flowers, the flower remains are discarded leading to a waste of resources.…”
Section: Introductionmentioning
confidence: 99%